2011
DOI: 10.1590/s0074-02762011000100011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of regulatory polymorphisms in the promoter region of the STAT6 gene in a Gabonese population

Abstract: Parasites remain competent invaders of host immunity. Their invasion strategies have proven to impact immunorelevant genes leading to diversity among gene families. We focussed on signal transducer and activator of transcription (STAT6) factor that plays a fundamental role in signal transduction and activation of transcription. Recent studies have highlighted the role of STAT6 variants in control of infection levels. We identified and investigated regulatory single nucleotide polymorphisms (SNPs) in the promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Earlier studies have identified some regulatory SNPs on the promoter loci of these five genes from 40 unrelated Gabonese individuals who had earlier infection episodes with various parasites, including P. falciparum [14,19-21]. These SNPs were then validated for their allelic gene expression using transient transfection assays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have identified some regulatory SNPs on the promoter loci of these five genes from 40 unrelated Gabonese individuals who had earlier infection episodes with various parasites, including P. falciparum [14,19-21]. These SNPs were then validated for their allelic gene expression using transient transfection assays.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the identified were already pre-described, while others were newly discovered. All the SNPs selected for the current investigation were found to alter expression of their respective gene [14,19-21]. Therefore any possible correlations of these SNP variants with resistance or susceptibility to mild malaria attacks and/or the control of P. falciparum infection levels were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crippling effect of host immunity on onset of an infection is due to the fact that parasites induce Tregs that in turn suppress antiparasite effector cells [4]. The Tregs are a subset of T cells that function to control immune responses.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…The single-nucleotide polymorphisms (SNPs) in the promoter region of the genes such as STAT6 , Foxp3 , and TNFRSF18 were well characterized for their functional role [4, 10, 83]. One gene of interest that plays a key role in the function of Tregs is the IL-10 gene locus.…”
Section: Regulatory Gene Polymorphismsmentioning
confidence: 99%